2016
DOI: 10.1515/mms-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

Classification of EEG Signals Using Adaptive Time-Frequency Distributions

Abstract: Time-Frequency (t-f) distributions are frequently employed for analysis of new-born EEG signals because of their non-stationary characteristics. Most of the existing time-frequency distributions fail to concentrate energy for a multicomponent signal having multiple directions of energy distribution in the t-f domain. In order to analyse such signals, we propose an Adaptive Directional Time-Frequency Distribution (ADTFD). The ADTFD outperforms other adaptive kernel and fixed kernel TFDs in terms of its ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Classification of ECoG signals plays an important role in many neurological studies, for example, for staging a neurologic disease or for brain-machine interface applications [29,30]. In this study, PCA was applied to ECoG, for highlighting how rats' brain codes different stimulus features [31].…”
Section: Discussionmentioning
confidence: 99%
“…Classification of ECoG signals plays an important role in many neurological studies, for example, for staging a neurologic disease or for brain-machine interface applications [29,30]. In this study, PCA was applied to ECoG, for highlighting how rats' brain codes different stimulus features [31].…”
Section: Discussionmentioning
confidence: 99%
“…Khan and Ali () proposed a time‐frequency domain based categorization of EEG signals. The authors achieved 97.5% of an average accuracy for the signals classifications.…”
Section: Related Workmentioning
confidence: 99%
“…Previous studies have shown that the ADTFD offers high resolution and can be used to estimate the instantaneous frequency of closely spaced signal components [33]. Due to its high resolution, the ADTFD has found applications in e.g., classification of EEG signals and direction of arrival estimation [34,35].…”
Section: Introductionmentioning
confidence: 99%